Perbandingan Teknik pada Struktur Sistem File Windows & Linux - Zacky Rafian Fawwauzy; Taufik Eka Albani; Elkin Rilvani (Asosiasi Riset Teknik Elektro dan Informatika Indonesia, 2025)
This research compares the techniques used in the file system structures of Windows and Linux. Each operating system employs distinct approaches to data organization, access, and management, as reflected in their respective file systems: NTFS for Windows and ext4 for Linux. The study explores the strengths, weaknesses, and applications of these systems under various conditions. By analyzing both theoretical documentation and empirical experiments, this research highlights the technical and philosophical aspects influencing the design and performance of file systems in Windows and Linux. The findings provide insights for selecting an appropriate file system based on specific requirements, emphasizing performance, reliability, and usability.